Synthesis of functional 1, 2-dithiolanes from 1, 3-bis-tert-butyl thioethers. Issue 33 (14th August 2020) - Scheutz, Georg M.; Rowell, Jonathan L.; Wang, Fu-Sheng; Abboud, Khalil A.; Peng, Chi-How; Sumerlin, Brent S.
Abstract : We report the one-step synthesis of diversely substituted functional 1, 2-dithiolanes by reacting readily accessible 1, 3-bis- tert -butyl thioethers with bromine. Abstract : We report the one-step synthesis of diversely substituted functional 1, 2-dithiolanes by reacting readily accessible 1, 3-bis- tert -butyl thioethers with bromine. The reaction proceeds to completion within minutes under mild conditions, presumably via a sulfonium-mediated ring closure. Using X-ray crystallography and UV-vis spectroscopy, we demonstrate how substituent size and ring substitution pattern can affect the geometry and photophysical properties of 1, 2-dithiolanes.